The importance of animal welfare and veterinary services in a changing world - Doyle, Rebecca; Wieland, Barbara; Saville, K.; Grace, Delia; Campbell, A.J.D. (World Organisation for Animal Health, 2021)
Animal welfare is an essential component of the future of sustainable agriculture and the United Nations Sustainable Development Goals. There is growing global recognition of the importance of animal welfare, which must always be considered as part of the decision-making around food and nutrition security. Veterinary Services, encompassing public and private veterinarians and para-veterinarians, are custodians of animal welfare and key players in future actions to improve it. The welfare of animals is everyone’s responsibility, from the individual farmer and practitioner to policymakers at the national and intergovernmental level. In this paper, after providing background information about current animal welfare issues and identifying animal welfare risks, the authors make a number of recommendations for action at the institutional and individual level. They do so because while the former is essential to generate change at scale and effective resourcing, the latter can create immediate action at a local level and drive change from the ground up. Without coordinated action from Veterinary Services, opportunities to improve animal welfare, alongside human and environmental health and well-being, may very well be lost, and animal welfare may fail to improve or even be at risk of decline.